THE IMPORTANCE OF REASON OF TOURISM EDUCATION IN IRANIAN SCHOOLS - LOTFI, Heydar; MOHSENINIA, İman (The Eurasia Proceedings of Educational and Social Sciences, 2015)
The accurate touch of life and living environment for every child is a requirement of growth. Adolescence period is between childhood (period of irresponsibility, irrationality and movements with many variable errors) and youth (a period in which individual shall enter the community and acquire many experiences and knowledge, in which the formed personality hardly changes). Tourism is an item promoting and completing this growth (Anderson, 1997). Since the developed countries perform the scientific and practical plans for this age range for having the specialist, aware, self-reliant youngsters but neither is there a system in Iran working in this range and giving us the living information, education and skills, nor does they have found out the value of this importance. They include the natural and wild sections, eco-farm and enclosed workshop space, and may solve the current problems of societies such as parents’ business, lack of good entertainment facilities and high expenses of travel for families which cause many parents in different reasons can’t provide suitable entertainment and amusement for their children. The results show that because many adults acquire knowledge in adulthood and they are not institutionalized in their origin, they will face problem in practice; therefore, they fail to undertake management position of a related system while childhood structure of a child will form correctly in terms of the environment, travel, nature and the child identity by developing the tourism and ecotourism schools so that they may progress in adulthood for sustainable development as an individual or citizen. Therefore, it is necessary for this age range to have a professional center. Even if we are willing to manage schools with a scientific approach, better we guide our children to a green and knowledgebase future and jobs as tourism and ecotourism schools are a good field for this purpose.